Educação popular e consciência sanitária : o movimento de educação de base (MEB) no sertão do Seridó Potiguar (1970-1980) - Siqueira, Juciene Raquel de Lima (2023)
This dissertation intended to investigate the trajectory of Popular Education in Health, through the Basic Education Movement (MEB), in the Seridó region of northern Rio Grande do Sul, in the 1970s and 1980s. formation of Sanitary Consciousness, through the Rural Radio Education Station of Caicó. The station created in May 1963, five months later incorporated the presence of MEB in its programming schedule. In the activities carried out by the MEB Caicó System, one can identify the grouping and non-directive meetings of young people and adults from the urban peripheries and the countryside; the formation of educational booklets; the conscientious approach to the subject's social role in the world; information and distribution of materials. The body responsible for the MEB was the National Conference of Bishops of Brazil (1952) with state funding. From the 1964 Military Coup, the MEB went through several internal and administrative crises that reflected in the program's guidelines and in the closure of some of its main Systems. With the political opening in the 1970s, one can again see awareness being incorporated into the programs and classes broadcast by the Issuer. For our purpose, educational programs from Radio Rural, magazines and newspapers published by MEB Nacional and Local, letters from newly literate students to the station, annual reports from the MEB Caicó System (headquarters city), booklets were consulted. We also used, to support our writing, the authors Freire, 1980; Kadt, 2013; Medeiros, 2008; Thompson, 1963. We can conclude that, through research, Popular Education for health revolutionized the lives of sertanejos from Seridó who, still plagued by the problems of drought, political neglect and poor distribution of land and income, were contemplated by the awareness process in the grid of radio programming.